Über einige neuseeländische Stratiomyiiden Osten-Sackens im Deutschen Entomologischen Institut in Berlin (Diptera). - Lindner, Erwin (Contributions to Entomology = Beiträge zur Entomologie, 1958)
The author deals with 11 species of Stratiomyiidae (Diptera). He dercribes as new 2 genera and 6 species. Nomenclatural Acts amoena Lindner, 1958 (Australoberis), spec. n. parvula Lindner, 1958 (Dysbiota), spec. n. osten-sackeni Lindner, 1958 (Neoexaireta), spec. n. smaragdina Lindner, 1958 (Neoexaireta), spec. n. venusta Lindner, 1958 (Neoexaireta), spec. n. Australoberis Lindner, 1958 (Stratiomyiidae), gen. n. Dysbiota Lindner, 1958 (Stratiomyiidae), gen. n.